World Politics in Translation (Taylor & Francis, 2025)
Virtually all pertinent issues that the world faces today – such as nuclear proliferation, climate change, the spread of infectious disease and economic globalization – imply objects that move. However, surprisingly little is known about how the actual objects of world politics are constituted, how they move and how they change while moving. This book addresses these questions through the concept of 'translation' – the simultaneous processes of object constitution, transportation and transformation. Translations occur when specific forms of knowledge about the environment, international human rights norms or water policies consolidate, travel and change. World Politics in Translation conceptualizes 'translation' for International Relations by drawing on theoretical insights from Literary Studies, Postcolonial Scholarship and Science and Technology Studies. The individual chapters explore how the concept of translation opens new perspectives on development cooperation, the diffusion of norms and organizational templates, the performance in and of international organizations or the politics of international security governance. This book constitutes an excellent resource for students and scholars in the fields of Politics, International Relations, Social Anthropology, Development Studies and Sociology. Combining empirically grounded case studies with methodological reflection and theoretical innovation, the book provides a powerful and productive introduction to world politics in translation.